Runoff and Soil Loss Modelling for Rengali-Mandira Catchment - Sahoo, R.K.; Sahoo, N.; Sharma, S.D. (Journal of Soil and Water Conservation, 2022)
Environment management implies utilisation of natural resources without degrading their quality. In agriculture, the concern is to protect land from erosion and water rees.ti'oni pollution. Due to indiscriminate deforestation, the quality glaland is degrading at a faster rate. As main' potential agricultural pollution problems are related to soil loss and water movement management practices that prevent erosion and made efficient use of water will minimise these natural disaster. Before 1983, Rezzgali-Alandira catchment itias suffering from severe Soil and Water erosion hazards, due to which, Rengali reservoir and Mandira reservoir were silted heavily. As a result ofthus, the storage capacity of these reservoirs were reduced to a great extent. :Vier 1983. entire, Rengali-Mandira catchment was treated with different Soil and Water Conservation measures. For better planning and management of watersheds, the effect of different conservation measures on runoff and silt yield was studied. Hence, data of five selected watersheds of Rengali-Mandira Catchment i.e. monthly and annual rainfall, runoff silt production rate and catchment characteristics like drainage area, treatable area and topo elements were used to develop models by regression analysis. Models developed for runoff and silt production rate can be utilised in both similar gauged and ungauged watersheds to accelerate the quality of planning and management. The runoffand SPR (Silt production rate) models developed for .five selected watersheds can be carefully analysed for further development and management of ecosystems in the studied watersheds on sustainable basis.